Children’s understanding of the risks and benefits associated with research - Burke, T. M. (Journal of medical ethics, 2005)
Objective: The objective of the current study was to maximise the amount of information children and adolescents understand about the risks and benefits associated with participation in a biomedical research study. Design: Participants were presented with one of six hypothetical research protocols describing how to fix a fractured thigh using either a “standard” cast or “new” pins procedure. Risks and benefits associated with each of the treatment options were manipulated so that for each one of the six protocols there was either a correct or ambiguous choice. Participants and setting: Two hundred and fifty one children, ages 6-15 (53% boys), and 237 adults (30% men) were interviewed while waiting for a clinic appointment at the Hospital for Sick Children. Results: Using standardised procedures and questionnaires, it was determined that most participants, regardless of age group, were able to understand the basic purpose and procedures involved in the research, and most were able to choose the “correct” operation. The younger children, however, showed an overall preference for a cast operation, whereas the older participants were more likely to choose the pins. Conclusions: By creating age appropriate modules of information, children as young as six years can understand potentially difficult and complex concepts such as the risks and benefits associated with participation in biomedical research. It appears, however, that different criteria were used for treatment preference, regardless of associated risks; older participants tended to opt for mobility (the pins procedure) whereas younger participants stayed with the more familiar cast operation.